Angewandte Kulturwissenschaften – Überlegungen zum Studienprogramm einer akademischen Disziplin nach dem cultural turn im Hinblick auf berufliche Perspektiven - Wolting, Stephan (Glottodidactica, 2012)
The author tries to attract attention for the careers ant the education of that what we call applied Cultural Studies after the cultural turn in the Humanities. He refers to some empirical studies and tries to put it out how differs the several institutes especially in the German spoken academic world. After all the conclusion of the author could be that there is an big demand for specialists in the area of applied cultural studies. The formation or education has to refer widely to a conception or the terminus of every-day-culture, so that it could be a big help in economic, social and education professions.